2020
DOI: 10.1093/cid/ciaa1861
|View full text |Cite
|
Sign up to set email alerts
|

Infant Exposure to Dolutegravir Through Placental and Breast Milk Transfer: A Population Pharmacokinetic Analysis of DolPHIN-1

Abstract: Background Rapid reduction of HIV viral load is paramount to prevent peripartum transmission in women diagnosed late in pregnancy. We investigated dolutegravir population pharmacokinetics in maternal plasma, cord, breastmilk and infant plasma of DolPHIN-1 participants (NCT02245022) presenting with untreated HIV late in pregnancy (28-36 weeks gestation). Methods Pregnant women from Uganda and South Africa were randomised (1:1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…The infant concentrations of other ARVs were consistent with previous data showing differential exposure with very low or undetectable levels for lamivudine, 4 , 23 emtricitabine, tenofovir derived from tenofovir disoproxil fumarate 25 and raltegravir, 29 whereas efavirenz, nevirapine and dolutegravir were shown to be detectable in infants. 4 , 30 , 31 We observed that dolutegravir levels in the infant are comparable or higher than levels measured in the breastmilk, as also reported previously. 30 , 31 This observation relates to the fact that dolutegravir is mainly metabolized by UGT1A1, a drug-metabolizing enzyme whose immaturity, particularly in preterm infants, can result in slow elimination of the drug.…”
Section: Discussionsupporting
confidence: 90%
“…The infant concentrations of other ARVs were consistent with previous data showing differential exposure with very low or undetectable levels for lamivudine, 4 , 23 emtricitabine, tenofovir derived from tenofovir disoproxil fumarate 25 and raltegravir, 29 whereas efavirenz, nevirapine and dolutegravir were shown to be detectable in infants. 4 , 30 , 31 We observed that dolutegravir levels in the infant are comparable or higher than levels measured in the breastmilk, as also reported previously. 30 , 31 This observation relates to the fact that dolutegravir is mainly metabolized by UGT1A1, a drug-metabolizing enzyme whose immaturity, particularly in preterm infants, can result in slow elimination of the drug.…”
Section: Discussionsupporting
confidence: 90%
“…DTG levels were measured in maternal plasma during prenatal and postnatal period, up to postnatal day (PND) 21. As DTG is known to transfer to infants through milk in addition to transplacental transfer [40][41][42], maternal plasma drug levels were measured up to the day of weaning of pups (PND 21). At GD 8.5 and 16.5, high DTG concentrations were detected in plasma of dams, 38,628.63 ± 4855.53 and 27,296.3 ± 2701.15 ng/ mL, respectively (Fig.…”
Section: Biodistribution Of Dtg To Developing Brain During Gestationmentioning
confidence: 99%
“…popPK parameter estimates of DTG were in agreement with values reported in the literature. [12][13][14] In DTGnaïve infants, a 5-mg DTG dose at birth with a second dose after 48 hours maintained median concentrations above the lower bound of the target range (0.77 mg/mL) and below the upper bound of the target range (7.34 mg/mL representing 2fold above the adult Cmax value). In DTG-exposed infants, a 5-mg DTG dose at 24 hours after birth with a second dose after 48 hours maintained median concentrations within or nearly within the target range, even if the last maternal DTG dose was taken as soon as 6 hours or as long as 24 hours before delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Based on limited data, DTG is detectable in small amounts of breast milk but not likely to contribute significantly to DTG plasma concentrations in the neonate, whereas breastfeeding infants have higher plasma bilirubin concentrations. 13,22 However, acquisition of DTG through breast milk was not considered in this analysis. Finally, a limited range of maternal and neonatal dosing scenarios was explored.…”
Section: Discussionmentioning
confidence: 99%